Understanding the ASEAN Way in the Thailand–Cambodia Border Conflict: Insights from Structuration Theory and the Four Flows Model - Ani Nigeriawati; Joevi Rudyarti; Hafied Cangara (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2026)
This study examines the relevance of the ASEAN Way in managing the Thailand–Cambodia border conflict through the lens of Structuration Theory and McPhee and Zaug’s Four Flows Model. Using a qualitative case study design, data were collected from document analysis and an in-depth interview with an ASEAN diplomat. Thematic analysis was employed to identify communication patterns that shape interactions among member states. The findings show that the ASEAN Way is reproduced through four communicative flows (membership negotiation, self-structuring, activity coordination, and institutional positioning), which collectively form ASEAN’s diplomatic and social structure. The Thailand–Cambodia conflict demonstrates that consensus, non-interference, and informal communication networks remain central to ASEAN’s mediation approach, even though formal mechanisms like the ASEAN High Council were not activated. The study concludes that the ASEAN Way remains relevant but requires institutional learning and the development of more responsive conflict-management mechanisms.